Peningkatan Menulis Teks Deskripsi melalui Teknik Pertanyaan Panduan di MTs Hidayatul Husna: Improving writing description texts through the guiding question technique at MTs Hidayatul Husna - Hanifiyah, Siti Umi; Rokhmansyah, Alfian (Journal of Literature and Education, 2023)
Many students experience difficulties in writing, one of which is when writing descriptive text. This study aimed to improve students' skills in writing descriptive texts using the guiding question technique. This research is a class action research with a total of two cycles. The activities of each cycle include action planning, action implementation, observation or evaluation, and reflection. The subjects of this study were 15 students of class VII MTs Hidayatul Husna. Data was collected using the test method, while descriptive statistics were used in data analysis techniques. The results showed that the application of the guiding question technique was able to improve students' writing skills. It can be seen from the increase in completeness that occurred in cycle 1 to cycle 2, which rose from 60% to 86.67%. The conclusion is that students' writing related to descriptive text has improved after using the guiding question technique at MTs Hidayatul Husna.